Design of a New Terahertz Nanowaveguide Amplifier - Michal Cada; Jaromir Pistora (IEEE Photonics Journal, 2017)
A novel amplifier is proposed based on a nanostructured waveguide supporting terahertz waves. A lateral pin photodiode structure, biased with a dc voltage and illuminated by a continuous-wave light, serves as an amplifying medium whereby drifting light-generated electrons provide energy required for amplification. Interaction between the propagating terahertz guided wave and the drifting electron stream is analyzed, and a dispersion equation is derived. Real life parameters of silicon are used to demonstrate and illustrate the achievable performance. Doubling of the wave power over only one micrometer is shown to be feasible even when all loss mechanisms are considered.